2014
DOI: 10.1186/2045-4015-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies for existencial and spiritual suffering in Israeli patients with advanced cancer

Abstract: Coping with existential and spiritual concerns is inescapable in end-of-life care although not enough is known about the strategies and mechanisms involved. This pilot study focused on identifying the strategies for coping with existential and spiritual suffering at the end of life of secular Jews with advanced-stage cancer. Using the phenomenological approach to data collection, in-depth interviews were conducted with 22 patients receiving symptom relief care at a daycare oncology clinic. The interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…As the study by Bentur et al [3] only evaluated "secular" Israelis, it will be important to do similar studies with the segment of Jewish population that identifies itself as religious, as well on non-Jewish patients, although as discussed above, based on the comparison of the results of this study with the one by Blinderman and Chernys [4], it is likely that the results will not be very different.…”
Section: Spiritual Care In Israelmentioning
confidence: 92%
See 3 more Smart Citations
“…As the study by Bentur et al [3] only evaluated "secular" Israelis, it will be important to do similar studies with the segment of Jewish population that identifies itself as religious, as well on non-Jewish patients, although as discussed above, based on the comparison of the results of this study with the one by Blinderman and Chernys [4], it is likely that the results will not be very different.…”
Section: Spiritual Care In Israelmentioning
confidence: 92%
“…Regarding spiritual and existential coping strategies, the topic of the paper by Bentur et al [3], there is a significant body of research already available defining coping mechanisms in Western society as well as studies evaluating how these strategies affect the ability of advanced cancer patients to adjust to illness [19,20]. This has led to the development of recommended therapeutic intervention protocols [5,[21][22][23], with studies evaluating these interventions for effectiveness currently underway [24].…”
Section: Spiritual Care In the United Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, religion gives meaning to people's life and death, and as a result creates an inner peace and reduces suffering in people (17). Another study showed a significant and positive relationship between religious beliefs and pain reduction (18). Beiranvand concluded that religious and spiritual interventions, including prayer and meditation, can be applied as a non-pharmaceutical pain management technique to reduce pain and increase calmness after a C-section (19).…”
Section: Introductionmentioning
confidence: 99%